Treatment of neuromyelitis optica: Review and recommendations - Kimbrough, D; Fujihara, K; Jacob, A; Lana-Peixoto, M; Isabel Leite, M; Levy, M; Marignier, R; Nakashima, I; Palace, J; De Seze, J; Stuve, O; Tenembaum, SN; et al. (Elsevier, 2012)
Neuromyelitis optica (NMO) is an autoimmune demyelinating disease preferentially targeting the optic nerves and spinal cord. Once regarded as a variant of multiple sclerosis (MS), NMO is now recognized to be a different disease with unique pathology and immunopathogenesis that does not respond to traditional MS immunomodulators such as interferons. Preventive therapy in NMO has focused on a range of immunosuppressive medications, none of which have been validated in a rigorous randomized trial. However, multiple retrospective and a few recent prospective studies have provided evidence for the use of six medications for the prevention of NMO exacerbations: azathioprine, rituximab, mycophenolate mofetil, prednisone, methotrexate and mitoxantrone. This review provides a comprehensive analysis of each of these medications in NMO and concludes with a set of recommended consensus practices. Copyright 2012 Elsevier B.V.